A realistic validation study of a new nitrogen multiple-breath washout system. - Florian Singer; Birgitta Houltz; Philipp Latzin; Paul Robinson; Per Gustafsson (PLoS ONE, 2012)
Background For reliable assessment of ventilation inhomogeneity, multiple-breath washout (MBW) systems should be realistically validated. We describe a new lung model for in vitro validation under physiological conditions and the assessment of a new nitrogen (N(2))MBW system. Methods The N(2)MBW setup indirectly measures the N(2) fraction (F(N2)) from main-stream carbon dioxide (CO(2)) and side-stream oxygen (O(2)) signals: F(N2) = 1-F(O2)-F(CO2)-F(Argon). For in vitro N(2)MBW, a double chamber plastic lung model was filled with water, heated to 37°C, and ventilated at various lung volumes, respiratory rates, and F(CO2). In vivo N(2)MBW was undertaken in triplets on two occasions in 30 healthy adults. Primary N(2)MBW outcome was functional residual capacity (FRC). We assessed in vitro error (√[difference](2)) between measured and model FRC (100-4174 mL), and error between tests of in vivo FRC, lung clearance index (LCI), and normalized phase III slope indices (S(acin) and S(cond)). Results The model generated 145 FRCs under BTPS conditions and various breathing patterns. Mean (SD) error was 2.3 (1.7)%. In 500 to 4174 mL FRCs, 121 (98%) of FRCs were within 5%. In 100 to 400 mL FRCs, the error was better than 7%. In vivo FRC error between tests was 10.1 (8.2)%. LCI was the most reproducible ventilation inhomogeneity index. Conclusion The lung model generates lung volumes under the conditions encountered during clinical MBW testing and enables realistic validation of MBW systems. The new N(2)MBW system reliably measures lung volumes and delivers reproducible LCI values.